Vzročna zveza med naravo in pravom - Svetlič, Rok (Podjetje in delo, 2025)
The discussion is devoted to the problem of causality, as it lies between natural phenomena and legal discourse. We will focus on the approaches proposed by the theories of natural and legal causality. We will point out their shortcomings and explain the reasons why the theory of adequate causality has become dominant today. The discussion pays special attention to the differences between the theory of adequate causality and the theory of ratio legis of causality, to makes visible the specific relations of the theories of causality to the natural dimension of the conduct of a legal subject and its consequences: natural causality is a priori limited only to the natural dimension, the theory of adequate causality derives from natural causality and at the same time reaches beyond it through legal reasoning, while the theory of ratio legis tries to completely eliminate the dimension of naturalness from the institute of causality. The article shows that in this way the theory of ratio legis is caught in a tautology, which is why it fails in its task. A more detailed analysis demonstrates that this theory still plays an important role for a civil tort, but not at the level of causation, but rather at a level analogous to the principle of legality in criminal law.